Seismic anisotropy beneath eastern China from shear wave splitting. Issue 3 (27th May 2019) - Yang, Xiaoyu; Li, Hongyi; Li, Yonghua; Lü, Qingtian; Zhang, Guibing; Jiang, Guoming; Li, Xinfu
SUMMARY: We examine seismic anisotropy beneath eastern China by analysing shear wave splitting of teleseismic SKS, SKKS and PKS phases recorded at 402 permanent and temporary stations. In general, our fast directions are approximately oriented in the E–W direction. The delay times vary greatly between 0.5 and 1.9 s. The delay times at stations in the Sichuan basin are less than 0.8 s, which could explain the fossilized anisotropy in the lithospheric mantle and little deformation after the formation of stable block. The fast directions in the Qinling–Dabie orogenic belts orient NWW–SEE, E–W and NEE–SWW, and are roughly parallel to the strikes of orogens that may indicate that the anisotropy contribution comes mainly from the lithospheric mantle. The fast directions mostly oriented in the nearly E–W direction, are generally subparallel to the absolute plate motion directions beneath the North China Craton and South China Block, suggesting it is primarily related to drag induced by the asthenospheric flow.